2021
DOI: 10.3847/psj/ac390a
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Figures to the Seventh Order and the Interiors of Jupiter and Saturn

Abstract: Interior modeling of Jupiter and Saturn has advanced to a state where thousands of models are generated that cover the uncertainty space of many parameters. This approach demands a fast method of computing their gravity field and shape. Moreover, the Cassini mission at Saturn and the ongoing Juno mission delivered gravitational harmonics up to J 12. Here we report the expansion of the theory of figures, which is a fast method for gravity field and shape computation, to the seventh order (ToF7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 73 publications
4
49
3
Order By: Relevance
“…Saturn was found to have a fuzzy core when accounting for EoS perturbations: then the core extends to ∼ 0.4R Sat , a result that is more consistent with the solution of Mankovich & Fuller (2021). As discussed in detail in (Nettelmann et al 2021), such a structure model corresponds to a dilute core and helium rain, which together result in a large region in Saturn's deep interior that is inhomogeneous in composition and is stable against convection.…”
Section: Saturnmentioning
confidence: 54%
See 4 more Smart Citations
“…Saturn was found to have a fuzzy core when accounting for EoS perturbations: then the core extends to ∼ 0.4R Sat , a result that is more consistent with the solution of Mankovich & Fuller (2021). As discussed in detail in (Nettelmann et al 2021), such a structure model corresponds to a dilute core and helium rain, which together result in a large region in Saturn's deep interior that is inhomogeneous in composition and is stable against convection.…”
Section: Saturnmentioning
confidence: 54%
“…Overall, the total heavy-element mass in Jupiter can range between ∼ 20-60 M ⊕ (Helled 2019). Interestingly, it was recently shown that the high-order J n of the Jupiter models fall along the same line in J n -J n+2 space, regardless of detailed model assumptions and the H-He EOS used (Guillot et al 2018;Nettelmann et al 2021). Nettelmann et al Nettelmann et al (2021) found that J 6 stands out in that it is neither adjusted, as J 2 and J 4 are, nor insensitive to interior model assumptions, as the higher order J n n ≥ 8 are.…”
Section: Empirical Eosmentioning
confidence: 99%
See 3 more Smart Citations